Association of socioeconomic and clinical variables with the state of frailty among older inpatients - Darlene Mara dos Santos Tavares; Isabella Danielle Nader; Mariana Mapelli de Paiva; Flavia Aparecida Dias; Maycon Sousa Pegorari (Universidade de São Paulo, 2015)
Objectives: to identify the prevalence of frailty among inpatient older adults in a clinical hospital and check the association of the socioeconomic and clinical characteristics with the state of frailty. Method: observational, cross-sectional and analytical study, conducted with 255 hospitalized patients. Materials used: structured instrument for the economical and clinical data and frailty phenotype of Fried. Descriptive and bivariate statistical analysis was carried out and, by means of chi-square tests and ANOVA One-way (p<0.05). Results: the prevalence of frailty corresponded to 26.3%, while pre-frailty represented 53.3%. The highest proportion of frail seniors was identified for 80 years or older (p = 0.004), widowed (p = 0.035) and with the highest average length of stay (p = 0.006). Conclusion: inpatient older adults presented high percentages of frail states associated with socioeconomic variables and hospitalization period. The identification of the health conditions related to pre-frailty and frailty can foster the planning and implementation of the assistance to older adults in this context.